DUAL FINANCIAL PRESSURES AND FRAUD RISK AMONG THE SANDWICH GENERATION IN BANKING - Djibran, Fauzi (Integrative Perspectives of Social and Science Journal, 2025)
In the banking industry, this group faces more complex challenges due to the nature of their work, which demands high professionalism, financial stability, and integrity in managing funds and financial transactions. The purpose of this study is to examine how dual financial pressures experienced by the sandwich generation in the banking sector can increase the risk of involvement in fraudulent activities and to identify the key factors influencing individuals in this generation to engage in or avoid fraud in the banking environment. This research employs a descriptive qualitative method. The findings indicate that fraud mitigation efforts in the banking sector must be conducted comprehensively and sustainably. With the right approach, banking institutions can significantly reduce fraud risks, improve employee well-being, and maintain customer and stakeholder trust in the stability and credibility of the financial industry.